2017
DOI: 10.1021/acsami.7b03160
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Orientation Matters: Longer-Circulating Choline Phosphate than Phosphocholine Liposomes for Enhanced Tumor Targeting

Abstract: Zwitterionic phosphocholine (PC) liposomes are widely used in drug delivery because of their high biocompatibility and long blood circulation time. We herein report that by flipping the direction of the PC dipole, the resulting choline phosphate (CPe) liposomes have an even longer circulation time, as confirmed at both cellular and animal-model levels. Even when 33% cholesterol was included in the lipid formulation with a poly(ethylene glycol) layer, the CPe liposome still had a longer blood circulation time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…The above discussions reflected that geometry of Phosphorylcholine was affected by the direction of electric fields. Atomic charge is related to the nature of covalent linkage and Wang et al reported that the phosphate group in Phosphorylcholine could bond to the surface of titanium dioxide (TiO 2 ), iron oxides (Fe 3 O 4 ), and zinc oxides (ZnO) because the oxygen in lipid phosphate performs a nucleophilic attack at the metal center forming a covalent linkage. The results showed that the phosphate (P) atom was generally electron donor and oxygen and hydrogen (O–H) atoms were electron acceptors that play an important part in metal oxides binding ability while electric field changes (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The above discussions reflected that geometry of Phosphorylcholine was affected by the direction of electric fields. Atomic charge is related to the nature of covalent linkage and Wang et al reported that the phosphate group in Phosphorylcholine could bond to the surface of titanium dioxide (TiO 2 ), iron oxides (Fe 3 O 4 ), and zinc oxides (ZnO) because the oxygen in lipid phosphate performs a nucleophilic attack at the metal center forming a covalent linkage. The results showed that the phosphate (P) atom was generally electron donor and oxygen and hydrogen (O–H) atoms were electron acceptors that play an important part in metal oxides binding ability while electric field changes (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Other in vivo studies also report on kinetics of tumor targeting of fluorescent liposomes within 5-8 hi ns imilar models,b ut these were done at 400 higher liposome concentrations yielding only 2-fold higher accumulation compared with whole body accumulation. [11] Thus water as ap H-responsive functionality is not only superior to other drug-nanocarriers to self-target an infection site,b ut also for self-targeting atumor site.Superior self-targeting of DCPA-H 2 Oliposomes was accompanied by better therapeutic efficacyi namurine, infected wound-healing model. Tail-vein injection of as uspension of ciprofloxacin-loaded DCPA-H 2 Ol iposomes in PBS yielded significantly better eradication of S. aureus from infected wounds than tail-vein injection of clinically applied ciprofloxacin in solution or suspensions of ciprofloxacinloaded DPPC or DCPM liposomes (Figure S11).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Most liposomal drug-loaded nanocarriers possess an umber of unique features,t hat include long circulation times in the blood without reticulo-endothelial rejection [10] and easy entry into tumor cells or infectious bacteria by fusion with the cell membrane. [11] Equipping lipid nanocarriers with pHresponsive functionalities to make them self-targeting to an acidic environment is not trivial however. pH-responsive, liposomal drug carriers have been made using weakly alkaline or zwitterionic lipids [12] with amino and carboxyl as functional groups,b ut they all have points of zero charge below pH 6.5 and their charge properties only respond to apHchange after several tens of minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most liposomal drug‐loaded nanocarriers possess a number of unique features, that include long circulation times in the blood without reticulo‐endothelial rejection [10] and easy entry into tumor cells or infectious bacteria by fusion with the cell membrane. [11] Equipping lipid nanocarriers with pH‐responsive functionalities to make them self‐targeting to an acidic environment is not trivial however. pH‐responsive, liposomal drug carriers have been made using weakly alkaline or zwitterionic lipids [12] with amino and carboxyl as functional groups, but they all have points of zero charge below pH 6.5 and their charge properties only respond to a pH change after several tens of minutes.…”
Section: Introductionmentioning
confidence: 99%